Surface Modifications and Growth of Titanium Dioxide for Photo-Electrochemical Water Splitting - Alexander, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This outstanding thesis provides a wide-ranging overview of the growth of titanium dioxide thin films and its use in photo-electrochemicals such as water splitting. The context for water splitting is introduced with the theory of semiconductor-liquid junctions, which are dealt with in detail. In particular plasmonic enhancement of TiO2 by the addition of gold nanoparticles is considered in depth, including a thorough and critical review of the literature, which discusses the possible mechanisms that may be at work. Plasmonic enhancement is demonstrated with gold nanoparticles on Nb-doped TiO2. Finally, the use of temperature and pressure to control the phase and morphology of thin films grown by pulsed laser deposition is presented.
Introduction -- Literature Review -- Principles of Photo-electrochemical Cells -- Experimental Methods -- Results: Plasmonic Photocurrent with AuNP-TiO2 -- Electrochemistry of TiO2 - Rutile (110) -- TiO2 Thin Films on Fused Silica -- Epitaxial TiO2 Thin Films on Single Crystal Substrates -- Conclusions.
Keywords: Materials; Materials -- Analysis; Electrochemistry; Nanoscience; Materials Engineering; Characterization and Analytical Technique; Electrochemistry; Nanophysics